The Effects of Pore Size on Electrical Performance in Lithium-Thionyl Chloride Batteries - Wang, Danghui; Jiang, Jianhong; Pan, Zhiyi; Li, Qiming; Zhu, Jinliang; Tian, Li; Shen, Pei Kang (Frontiers in Materials, 2019)
Lithium-thionyl chloride batteries possess the highest specific energies of all of those commercially available batteries. These batteries also have high operating voltages, with stable outputs, wide operating temperature ranges, long storage lives, and are of low cost. The main limitation of lithium-thionyl chloride batteries is the low discharge capacity at high discharge rates, which limits their commercial uses. In this study, a porous cathode carbon support was prepared by introducing ammonia bicarbonate as a pore-forming agent. The porous cathode carbon support that formed was systematically characterized by BET, SEM, and XRD. The porous carbon support was then assembled into an ER18505M battery system to characterize the electrochemical performance of the battery. The effect of pore structure on the electrochemical performance was determined and revealed the preparation of a high capacity lithium-thionyl chloride battery with a high discharge rate.